Pengaruh Literasi Keuangan, Perilaku Keuangan Dan Pendapatan Terhadap Minat Generasi Milenial Di Brebes Dalam Berinvestasi - Dewi Safitri; Titi Rahmawati; Maftukhin Maftukhin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Financial literacy, financial behavior and income are driving factors for an individual to make an investment decision. This study aims to determine the influence of financial literacy, financial behavior and income on investment decisions. This research method is descriptive quantitative. The sampling technique uses the random sampling technique. analysis of the data used is multiple linear regression analysis, partial test, simultaneous test and coefficient of determination. The results of the study show that financial literacy has a positive and significant direction with a large influence of 48.6% on investment decisions, financial behavior has a positive and significant direction with a large influence 12.5% on investment decisions, income has a positive and significant direction with a 9.4% influence on investment decisions, financial literacy, financial behavior and income have a simultaneous influence on investment decisions of 65.1% and 34.9% in influenced by other factors or variables that are not examined.